2021
DOI: 10.1021/acsomega.1c02644
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Photodegradable Nanocomposite (BiOBr/ZnO/WO3) for the Degradation of Phenol Pollutants: Optimization and Experimental Design

Abstract: The degradation of environmental contaminants with photocatalysts has bright prospects for application in the control of pollution. In this study, BiOBr/ZnO/WO 3 heterojunctions have been documented to be reliable visible-light photocatalysts for phenol deterioration. X-ray diffraction, X-ray photoelectron spectroscopy, Fourier-transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, photoluminescence spectral analysis, electrochemical impedance sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Heterogeneous photocatalysts are solids that can promote catalytic reactions in the presence of light without being consumed in the process [77]. TiO 2 , ZnO, SnO 2 , ZrO 2 , SiO 2 , WO 3 , CeO 2 , and other semiconductor materials are employed in photocatalytic reactions and can be used as photocatalysts because of their capacity to decolorize dye-containing wastewater [78,79]. Out of all of them, ZnO emerges as one of the best photocatalysts due to its unique physicochemical properties.…”
Section: Zinc Oxide As Photocatalystmentioning
confidence: 99%
“…Heterogeneous photocatalysts are solids that can promote catalytic reactions in the presence of light without being consumed in the process [77]. TiO 2 , ZnO, SnO 2 , ZrO 2 , SiO 2 , WO 3 , CeO 2 , and other semiconductor materials are employed in photocatalytic reactions and can be used as photocatalysts because of their capacity to decolorize dye-containing wastewater [78,79]. Out of all of them, ZnO emerges as one of the best photocatalysts due to its unique physicochemical properties.…”
Section: Zinc Oxide As Photocatalystmentioning
confidence: 99%
“…Based on coupling between different oxides in ternary composites, a new strategy has emerged to improve the photoresponse and increase the harvesting of visible light spectrum, as well as support the separation of the charge carriers which trigger photocatalytic efficiency [22][23][24]. Ali et al [25] studied the photocatalytic properties of BiOBr/ZnO/WO 3 ternary nanocomposites for degradation of phenol. The authors found that this composite has a degradation efficiency of 90% for 50 mg/L phenol under visible-light illumination for 300 min.…”
Section: Introductionmentioning
confidence: 99%
“…However, synthesizing visible light active semiconductor materials is not sufficient as the recombination rate of charge carriers is very high due to the small band gap energy . This problem was addressed using various strategies, such as doping metals and nonmetals, , co-depositing metals on semiconductor surfaces, and coupling of two or more semiconductors to create binary , and ternary , heterojunctions. A key strategy in photocatalytic processes for pollutant degradation is the construction of type-II heterostructure composite photocatalysts by coupling appropriate semiconductors. , …”
Section: Introductionmentioning
confidence: 99%